Design guidelines of adaptive e-learning environment for students Rattana Bundit University - หัวไผ่ สุระชัย; พรมสวัสดิ์ พิมพ์ชนก; อุไรเวโลจนากร สมโภชน์ (Journal of Rattana Bundit University, 2018)
This research is the design guidelines of adaptive electronic learning system for students of Rattana Bundit University. The purposes of this research were: 1) to study the opinions which concerned the design guidelines of adjustable electronic learning systems for students at Rattana Bundit University, and 2) to present the designing guidelines of an adaptive electronics learning system for Rattana Bundit University’s students. The sampling group consisted of the undergraduate students at Rattana Bundit University. This research employed the purposive and voluntary sample methods for selecting 50 students. The research tool utilized to gather data included questionnaires about the opinions on the adaptive e-learning systems from students at Rattana Bundit University. The collected data was analyzed by using statistics including arithmetic mean and standard deviation. The research findings showed that the opinions on the components of an adaptive electronic learning system from students at Rattana Bundit University were as follows: the overall was at a high level with an average of 4.01. According to the students opinions, the findings contended that the design of an adapted electronic learning system on learning activity was at a high level with an average of 4.14, followed by the management system of teaching and learning activities was at a high level with an average of 4.10, and the role of learners was at a high level with an average of 4.04. For the teaching process on electronics adaptive learning system, the findings pointed out that every step was appropriated for students including the leading web-based teaching step and the evaluation step with an average of 4.06, 3.98 and 3.91, respectively.